Hvem er hvem i Klagesangene? - Stegelmann, Mette (Dansk Teologisk Tidsskrift, 2018)
In this article the different speaking voices and personae in Lamentations are analysed with the intention of uncovering their dialogical interactions and the effect they have on communicating the themes of the text. It is shown that there are four principal voices in Lamentations: the lamenter, Zion, the Man and the community. An essential element in the polyphony in Lamentations is the personifi cation of the principal voices. Here it is the persona of Zion who particularly asserts herself in her role as personifi ed city. She confronts God, who remains silent in the discourse. The absence of God which is one of the main themes in Lamentations, becomes more obvious in the dynamic interaction between the lamenter and Zion. The dialogical discourse in Lamentations communicates a many-faceted portrait of God which results in a corresponding many-sided theology.